Using Olive Cake as a Sustainable Ingredient in Diets of Lactating Dairy Cows: Effects on Nutritional Characteristics of Cheese - Attard, George; Bionda, Arianna; Litrenta, Federica; Lopreiato, Vincenzo; Di Bella, Giuseppa; Potortì, Angela Giorgia; Lo Turco, Vincenzo; Liotta, Luigi (Sustainability, 2024)
This study aimed to investigate the chemical composition, fatty acid profile and polyphenol content of Provola cheese made with cow’s milk from cows fed a diet incorporating olive cake. Cheese samples were analysed in different months in order to test diet and diet×season effects. The results show that the cheese composition was influenced by both factors. The most beneficial cheese from a human health point of view was produced with milk from cows fed the treatment diet in the spring. Supplementing the diet of dairy cows with olive cake reduced the atherogenic and thrombogenic indices while increasing the total polyphenols in the cheese product. With a 32.9% increase in polyphenols, the cheese from the TEST group has greater functional nutrients and properties than the cheese from the CTR group. The data show that, combining the benefits of a more sustainable production process with a better final product, the supplementation of dried and stoned olive cake in the dairy cow diet improves the nutritional and health composition of the cheese.